Challenges and incentives for adopting agroforestry systems: a case study with family farmers in Belterra, Pará, Brazil - Pauletto, Daniela; Martorano, Lucieta Guerreiro; Arco-Verde, Marcelo Francia; Leal, Relionan Pimentel; Magalhães, Kaio Ramon de Sousa; Silva, Ádria Fernandes da; Araujo, Anselmo Junior Correa; Lopes, Lucas Sérgio de Sousa (Sustainability in Debate, 2024)
The adoption of agroforestry systems (AFS) is challenging for Amazonian family farmers. The objective of this study was to characterise socioeconomic aspects and explore perspectives on the main challenges and incentives highlighted by family farmers involved in the Project of Forest Restoration Through Agroforestry Systems (Prosaf) in Belterra, Pará, Brazil. We conducted a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis of the project, focusing on 17 family farming properties ranging from 7 to 189 hectares, where agriculture serves as the primary source of income for 71% of participants. The SWOT analysis of the agroforestry systems (AFS) yielded 190 responses: "source of income" was the most frequently mentioned as Strength (18.2%), "cultural practices" and "technical assistance" as Weaknesses (both 18.1%); "infrastructure and resources" as Opportunity (21.4%), and "wildlife predation" as Threat (18.8%). The results demonstrate that AFS in Belterra generate income, improve resilience, and ensure food security but challenges such as insufficient technical assistance and water scarcity highlight the need for support and incentives to maintain this practice.